Fear of Crime Through the Ears of a Murderino: The Effect of True Crime Podcasts on Fear of Crime - Bailey, Elizabeth June (2017)
The purpose of this study was to explore levels and correlates of fear of crime among a sample of individuals who listen to true crime podcasts. An online survey was used to gauge respondents' levels of fear of crime before and after listening to a true crime audio podcast entitled My Favorite Murder. The survey also included items designed to measure some individual characteristics and personal experiences. Results indicate that some of these factors were related to listeners' fear of crime before, after, and/or the overall change in fear of crime levels from before exposure to after. Specifically, age, race, known victims, personal victimization history, and frequency of true crime podcast exposure were all associated with fear of crime in some way; type of residential area the respondent lived in was the only factor shown to have no important impact on fear of crime levels. There were interesting patterns where relationships did exist, in that one group showed lower levels of fear than other groups before listening to the podcast, but the same group then showed the most significant increase in fear of crime after listening to the audio podcast, meaning that characteristic had a greater impact on fear of crime for said group over others that may have presented higher levels of fear before listening to a specific podcast. The findings of this study indicate that exposure to true crime media does have an impact of fear of crime, but unlike studies on other types of media, regular exposure to true crime podcasts tend to lessen fear of crime. Future studies should explore further this relationship in order to determine if other true crime podcasts share this same relationship with fear and also determine how this regular exposure increases fear in listeners